Minimizing Costs in Near-Critical Bioethanol Extraction and Dehydration Processes - Paulo, Cecilia Inés (2012)
In the present work, we propose a model-based cost optimization for three capacities of bioethanol extraction-dehydration plants with supercritical propane. We consider alternative integration schemes between process streams as different nonlinear programming problems (NLP) for energy minimization. In particular, we analyze integration between a heat pump option for the top vapor of the first distillation column with the beer column reboiler, which can provide reduction in total energy consumption, as well as lower final product cost. Capital and operating costs were evaluated for the analyzed schemes. Thermodynamic predictions are performed with an upgraded group contribution with association equation of state (GCA-EOS). We demonstrate that ethanol dehydration with supercritical propane can be a sustainable alternative that is energetically and economically competitive with other technologies. © 2012 American Chemical Society.